Isolation of anti-idiotype minor capsid Human papillomavirus type 16 (HPV 16 L2) IgY from egg yolk as immunogen of HPV vaccine - EKA NONENG NAWANGSIH; SAYU PUTU YUNI PARYATI; JUSUF S. EFFENDY; SUNARJATI SUDIGDOADI; EDHYANA SAHIRATMADJA; DIKI HILMI; EVI SOVIA (Smujo International, 2017)
Nawangsih EN, Paryati SPY, Effendy JS, Sudigdoadi S, Sahiratmadja E, Hilmi D, Sovia E. 2017. Isolation of anti-idiotype minor capsid Human papillomavirus type 16 (HPV 16 L2) IgY from egg yolk as immunogen of HPV vaccine. Nusantara Bioscience 9: 282-287. A potential strategy for the production of safe protective vaccines for human papillomavirus (HPV) infection is to utilize antiids. Meanwhile, hyperimmunized hens could provide a convenient of specific immunoglobulin in their yolks (IgY). This study aimed to isolate IgY specific to anti-idiotype HPV 16 L2 from egg yolk which could be used for future alternative immunogen for HPV vaccine. Antibody anti-idiotype derived from chicken egg yolk that chickens immunized by HPV 16 L2 antibody. The antibodies were purified from immunized chicken egg yolk, then electrophoresis it using SDS-PAGE method to determine the molecular weight of IgY. To determine an amount of protein, we used fluorometer method and to confirm an existence of specific IgY using ELISA method. The results showed that the IgY preparation dissociated into three protein major bands with molecular weights of 180; 65; and 25 kD. The IgY and IgY specific concentration in eggs yolk increased until 8th week. After 8th week the levels decreased gradually. Samples derived from chickens immunized showed significantly higher concentrations of IgY and IgY specifics than control (p<0.05). These results suggested that chicken IgY could be a practical strategy in large-scale production of specific antibody anti-idiotype HPV 16 L2 for HPV Vaccine.